Exchange Rate Assessment for Sub-Saharan Economies - Aydin, Burcu (IMF Working Papers; Working Paper ;, 2010)
This paper provides an exchange rate assessment for sub-Saharan African economies by using methodologies similar to those developed by the International Monetary Fund's Consultative Group on Exchange Rate Issues. As in the World Economic Outlook (IMF, 2009a), the unbalanced panel dataset covers 182 countries from 1973 to 2014. We apply four methodologies to assess the fundamental exchange rate: macroeconomic balance, equilibrium real exchange rate, external sustainability, and purchasing power parity. Results show that the impact of macroeconomic fundamentals on the equilibrium real exchange rate is different for sub-Saharan African economies than for advanced and less advanced economies.